You're not from around here, are you? : a lesbian in small-town America - Blum, Louise A., 1960- (Living out., 2001)
"Put together 20 million frozen sperm, two funny women, and one impoverished stretch of Appalachia and what do you get? A wise and celebratory tale by Louise A. Blum, author of the critically acclaimed novel, Amnesty, who now uses her razor wit and deft precision to tell the story of her own life. With the help of a tiny sperm cell they call "Dad," she and her partner decide to have a child, unleashing a storm of controversy in their small town. From a glowing feature article in the family section of the local newspaper to the resulting prayer vigils on the village green, the town responds in radically different ways to their presence. A depiction of small-town life with all its comforts and its terrors, this memoir will speak to anyone who's ever felt like an outsider in America."--Jacket